Analysing Construction Trends in the European Union Using Geographic Information Systems - Low , Sui Pheng; Raphael , Benny; Lim , Soo Ping (Penerbit Universiti Sains Malaysia, 2008)
Geographic Information System (GIS) is a useful tool for storing and manipulating geographical information to analyse patterns, relationships, and trends in order to gain new insights to make better and more informed decisions. Using the power of spatial organisation to suggest causes, explanations and relationships is significantly more superior to other forms of data representation such as the table or graph. This paper examines the construction trends in the European Union (EU) by using GIS software as a computional and presentation tool. The performance trends of the construction market in EU countries relative to the Gross Domestic Product (GDP), population and other economic sectors such as agriculture and manufacturing for a 20-year period between 1985 and 2004 were evaluated using GIS. Many EU countries seem to have a relationship with construction among the variables considered. This suggests that GDP, population, agriculture, and manufacturing are important factors that affect the role and development of the construction industry within an economy. GIS representation also demonstrated that it is capable of highlighting unique trends and features for further detailed analysis to be carried out